The tissue inhibitors of metalloproteinases (TIMPs): an ancient family with structural and functional diversity. - Brew, K; Nagase, H (2010)
Tissue inhibitors of metalloproteinases (TIMPs) are widely distributed in the animal kingdom and the human genome contains four paralogous genes encoding TIMPs 1 to 4. TIMPs were originally characterized as inhibitors of matrix metalloproteinases (MMPs), but their range of activities has now been found to be broader as it includes the inhibition of several of the disintegrin-metalloproteinases, ADAMs and ADAMTSs. TIMPs are therefore key regulators of the metalloproteinases that degrade the extracellular matrix and shed cell surface molecules. Structural studies of TIMP-MMP complexes have elucidated the inhibition mechanism of TIMPs and the multiple sites through which they interact with target enzymes, allowing the generation of TIMP variants that selectively inhibit different groups of metalloproteinases. Engineering such variants is complicated by the fact that TIMPs can undergo changes in molecular dynamics induced by their interactions with proteases. TIMPs also have biological activities that are independent of metalloproteinases; these include effects on cell growth and differentiation, cell migration, anti-angiogenesis, anti- and pro-apoptosis, and synaptic plasticity. Receptors responsible for some of these activities have been identified and their signaling pathways have been investigated. A series of studies using mice with specific TIMP gene deletions has illuminated the importance of these molecules in biology and pathology.